POTENSI PARIWISATA SULAWESI TENGGARA SEBAGAI DIPLOMASI PUBLIK INDONESIA DALAM MENGHADAPI ERA MASYARAKAT EKONOMI ASEAN (MEA) - Andi Andreansyah (Mediasi: Journal of International Relations, 2018)
AbstractThis research aims at revealing the tourism potentials of Southeast Celebes as Indonesian public diplomacy to face Asean Economic Community. Indonesia is one of Asean countries that contributes to economic integration mentioned by Asean Economic Community. Asean Economic Community is free trade or single market activity among Asean countries that was agreed with goals to develop the economics of Asean countries. one of the Asean Economic Community vision is to make single tourism of Southeast Asian, and to improve the competitiveness the economy of Asean Countries. Therefore, each country of Asean must prepare themselves, to become a target market of another country. As the biggest one of maritime nation, Indonesia has many beautiful places for tourism and one of the best tourism is located in Southeast Celebes province. This province shows their potentials of tourism with the increase of tourist numbers every year. Moreover, Southeast Celebes is one of the ten priorities of Indonesian tourism destination. Therefore, Southeast Celebes tourism is able to become one of a mainstay to face Asean Economic Community. This research uses the qualitative methodology. The data were collected with observation, collecting, finding, library research and interpreting as technique of collecting data. The technique of data analysis uses descriptive analysis method. This research is based on Islamic worldview. The objective of the research is to analyze how the role of Southeast Celebes Tourism as an Indonesian Public Diplomacy in influencing public opinion toward national interest to face Asean Economic Community. Southeast Celebes potentials are able to be soft power asset of Indonesian public diplomacy. These potentials succeed in public diplomacy, and many foreigners are engaged in visiting to Southeast Celebes, and the visitors increase every year. The increase of visitor affects to foreign exchange income, local business of local society, and economic development. Keyword: Southeast Celebes; Tourism; Soft Power; Public Diplomacy; Asean Economic Community (AEC)